2022
DOI: 10.3390/rs14030518
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Chlorophyll Content of Maize over Phenotyping as a Proxy for Crop Health in Smallholder Farming Systems

Abstract: Smallholder farmers depend on healthy and productive crop yields to sustain their socio-economic status and ensure livelihood security. Advances in South African precision agriculture in the form of unmanned aerial vehicles (UAVs) provide spatially explicit near-real-time information that can be used to assess crop dynamics and inform smallholder farmers. The use of UAVs with remote-sensing techniques allows for the acquisition of high spatial resolution data at various spatio-temporal planes, which is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…The prime activity that locals of Swayimani partake in is semi-subsistence farming on their housing plots, which is a crucial form of livelihood sustenance and food security. The predominant crop types in Swayimani are white and yellow maize, sugarcane, tomatoes, amadumbe (taro), and sweet potato [28]. The smallholder farmers manually sow crop seeds and fertilise croplands with livestock manure.…”
Section: Study Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prime activity that locals of Swayimani partake in is semi-subsistence farming on their housing plots, which is a crucial form of livelihood sustenance and food security. The predominant crop types in Swayimani are white and yellow maize, sugarcane, tomatoes, amadumbe (taro), and sweet potato [28]. The smallholder farmers manually sow crop seeds and fertilise croplands with livestock manure.…”
Section: Study Site Descriptionmentioning
confidence: 99%
“…In recent years, unmanned aerial vehicles (UAVs) have become a popular field phenotyping platform for precision agricultural applications. UAV-based phenotyping is the measurement and analysis of plant characteristics in a far more advanced and detailed manner [23,24,[28][29][30][31][32][33][34][35]. UAVs mounted with very-high-resolution (VHR) cameras offer advanced crop image throughput analytics and are effective in overcoming the limitations of satellite imagery [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Brewer et al [13] estimated the efficacy of multi-spectral UAV images with the random forest machine learning technique for estimating the chlorophyll content of maize via different development stages. The result shows that the red-edge and near-infrared wavelength bands and vegetation indices derived from the wavelength are needed to estimate chlorophyll content under the maize phenotyping.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies presented the potential of using the UAV in maize studies such maize plant counting or maize growth surveillance [7,8]. Various findings also showed that the UAV could be used widely, due to the availability of flying in a certain altitude, frequently flights with different parameters and high-resolution results [9,10]. Different methods and tools were elaborated in maize plant studies, such as utilizing Faster-RCNN to detect maize plant density [11], the level of nitrogen and plant height by using machine learning approaches for example Random Forest (RF), or Support Vector Machine (SVM) [12].…”
Section: Introductionmentioning
confidence: 99%